Напряженно-деформированное состояние высотного здания при ветровом воздействии и прогрессирующем обрушении - Semenov, A A; Porivaev, I A; Kuznetcov, D V; Nguen, T H; Saitgalina, A S; Tregubova, E S (Stroitel'stvo unikal'nyh zdanij i sooruhenij, 2017)
The subject of research is Idel Tower, the first high-rise building in the Republic of Bashkortostan. This study present the strength calculation of load bearing members of high-rise building under wind load and progressive collapse for structural analysis. The calculations were performed in software SCAD 21.1. The results were obtained as the natural mode shapes of building oscillation that may cause resonance, the maximum displacements under static and dynamic wind loads and ratios of normal forces caused by wind load to overall loads. The worst emergency situations were detected. The determination of the amount of reinforcements for ensuring the safety of people in emergencies for this building has also shown in this study.